Membentuk Wirausahawan Digital: Peran Literasi Digital, Pendidikan Kewirausahaan, dan Inovasi Personal - Elyvan Ruslie; Lydiawati Soelaiman (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
The rapid development of technology has pushed entrepreneurship towards digital. Even though the level of digital skills of people in Indonesia is in a relatively high category, the use of technology for entrepreneurial activities tends to still be low. The purpose of this study is to determine the effect of digital literacy and entrepreneurship education on students' digital entrepreneurship intentions in Bandar Lampung City, with personal innovation as a mediating factor. This study used a descriptive design with a quantitative approach, employing purposive sampling. The study included 123 students in Bandar Lampung who were actively studying and had taken entrepreneurship courses. The research instrument was developed using Google Forms and distributed online via a link shared via the WhatsApp application. The collected information was then processed using the SmartPLS 4 application. Data analysis showed that digital literacy, entrepreneurship education, and personal innovation had a positive and significant impact on digital entrepreneurship intentions. Furthermore, personal innovation plays an important role as a bridge in explaining the relationship between digital literacy, entrepreneurship education, and digital entrepreneurship intentions.